2009
DOI: 10.1161/strokeaha.109.557330
|View full text |Cite
|
Sign up to set email alerts
|

Statin Treatment and Stroke Outcome in the Stroke Prevention by Aggressive Reduction in Cholesterol Levels (SPARCL) Trial

Abstract: on behalf of the SPARCL InvestigatorsBackground and Purpose-Laboratory experiments suggest statins reduce stroke severity and improve outcomes. The Stroke Prevention by Aggressive Reduction in Cholesterol Levels (SPARCL) trial was a placebo-controlled, randomized trial designed to determine whether treatment with atorvastatin reduces strokes in subjects with recent stroke or transient ischemic attack (nϭ4731). We analyzed SPARCL trial data to determine whether treatment favorably shifts the distribution of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
72
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 34 publications
6
72
0
3
Order By: Relevance
“…25 A retrospective observational study reported that 1-year survival rates among patients with ischemic stroke who were administered statins before or during admission were higher than the counterparts. 6 About disability outcomes, the subanalysis of SPARCL Trial also showed that statin administration at nonacute phase was associated with reduced disability measured by mRS. 26 Another non-RCT found that statin withdrawal for 3 days after ischemic stroke onset in patients previously on statins was associated with significantly worse disability status after 90 days compared with patients receiving statins immediately after onset. 4 Thus, statin withdrawal at acute phase or nonadministration at nonacute phase should be associated with worse outcomes in patients with acute ischemic stroke, but the clinical significance of early administration to naive patients should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…25 A retrospective observational study reported that 1-year survival rates among patients with ischemic stroke who were administered statins before or during admission were higher than the counterparts. 6 About disability outcomes, the subanalysis of SPARCL Trial also showed that statin administration at nonacute phase was associated with reduced disability measured by mRS. 26 Another non-RCT found that statin withdrawal for 3 days after ischemic stroke onset in patients previously on statins was associated with significantly worse disability status after 90 days compared with patients receiving statins immediately after onset. 4 Thus, statin withdrawal at acute phase or nonadministration at nonacute phase should be associated with worse outcomes in patients with acute ischemic stroke, but the clinical significance of early administration to naive patients should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] The Stroke Prevention with Aggressive Reductions in Cholesterol Levels (SPARCL) trial showed a trend toward less severity for outcome 90 days after stroke with atorvastatin administration (80 mg), compared with placebo, in patients having a stroke during the trial. 10 So far, few studies have assessed the efficacy and safety of statin treatment in ischemic stroke patients treated with IV thrombolysis. Two recent meta-analyses showed that prior statin use may increase the risk of symptomatic intracerebral hemorrhage (sICH) within 36 hours after IV recombinant tissue plasminogen activator (rtPA), though without influencing 3-month functional outcome.…”
mentioning
confidence: 99%
“…7 Although this analysis was post hoc, and not clearly supported by benefit measured by the National Institutes of Health Stroke Scale and Barthel Index, these data are the largest to date in a randomized trial of treatment with a standardized high-dose statin in the acute phase at stroke onset. This intriguing signal from SPARCL, when combined with supportive experimental and epidemiological data, suggests that more randomized trials of acute statin therapy are needed.…”
Section: See Related Article P 3057mentioning
confidence: 86%